Consumer protection in Kosovo law compared to Islamic jurisprudence - Hajdini, Zenel Vesel (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed at clarifying the most important rights for consumer protection in Kosovan law and comparing them with Islamic jurisprudence. Legal, and the comparative approach between the Kosovar and Islamic laws, as required by the nature of the research. The study concluded that the Kosovar law provides full protection to consumers, which is consistent in the general framework with Islamic law.
Keywords: Kosovar law; Islamic jurisprudence; consumer protection